Multi-state discrimination below the quantum noise limit at the single-photon level. (December 2017) - Ferdinand, A.; DiMario, M.; Becerra, F.
Abstract Measurements approaching the ultimate quantum limits of sensitivity are central in quantum information processing, quantum metrology, and communication. Quantum measurements to discriminate multiple states at the single-photon level are essential for optimizing information transfer in low-power optical communications and quantum communications, and can enhance the capabilities of many quantum information protocols. Here, we theoretically investigate and experimentally demonstrate the discrimination of multiple coherent states of light with sensitivities surpassing the quantum noise limit (QNL) at the single-photon level under realistic conditions of loss and noise based on strategies implementing globally-optimized adaptive measurements with single photon counting and displacement operations. These discrimination strategies can provide realistic advantages to enhance information transfer at low powers, and are compatible with photon number resolving detection, which provides robustness at high powers, thus allowing for surpassing the QNL at arbitrary input power levels under realistic conditions. Quantum measurements: surpassing conventional sensitivity limits at low powers Light has intrinsic quantum noise, which limits how well we can measure it, especially at low powers, and bounds how much information we can communicate. A team led by F. Elohim Becerra at the University of New Mexico demonstrated optimized measurements for light pulses with different phases at low powers, such as those used in coherent optical communication. These optimized measurements can surpass the ultimate sensitivity limits of ideal conventional detectors, even in the presence of loss and noise encountered in realistic situations. The measurements are based on combining the input pulse with a reference field, and counting single photons in a fraction of the pulse. By analyzing the detection outcome, the reference field can be optimized to enhance the measurement's sensitivity. Optimized measurements at low powers may lead to more-efficient optical communication in realistic environments.